1970
DOI: 10.1002/macp.1970.021390116
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of unperturbed chain dimensions of macromolecules from intrinsic viscosity data

Abstract: An attempt has been made to examine the applicability of the methods, proposed b! KAMIDE et al. and STOCKMAYER and FIXMAN, for evaluating the unperturbed chain dimensions of macromolecules from intrinsic viscosity data. In the method of KAMIDE et al., the FLORY'S K value is evaluated from the parameters K, and a in the intrinsic viscositymolecular weight relation (the KUHN-MARK-HOUWINK-SAKURADA equation) expressed by[q] = Km.Ma, which should be established in two or more solvents for a given series of fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

1975
1975
1985
1985

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
(2 reference statements)
2
11
1
Order By: Relevance
“…This expectation was experimentally in part confirmed by measurements of Mw (by the light scattering in trifluoroacetic acid at 30°C) and of Mn (by the membrane osmometry in o-chlorophenol at 45°C) on several fractions. In this case, an increase in Mw/ Mn by combination of the polymer fractions of similar [11] Mn was determined from limc-o rr/C (C, concentration) by extrapolating the plot of rr/C vs. C. Meyerhoff and Shimotsuma3 concluded that Mn, determined by membrane osmometry in o-chlorophenol and m-cresol, is less reliable because of permeation of low molecular weight components through membrane (Sartorius ultracellafilter allerfeinst grade), which was indirectly deduced from the experimental fact that Mn by membrane osmometry is larger than Mn by end group analysis. In this study, for both PET and PEPC solutions, rr value was maintained constant at least several hours and the height of the solvent cup for solvent/solvent combination was not significantly variated.…”
Section: Fractionationmentioning
confidence: 99%
See 4 more Smart Citations
“…This expectation was experimentally in part confirmed by measurements of Mw (by the light scattering in trifluoroacetic acid at 30°C) and of Mn (by the membrane osmometry in o-chlorophenol at 45°C) on several fractions. In this case, an increase in Mw/ Mn by combination of the polymer fractions of similar [11] Mn was determined from limc-o rr/C (C, concentration) by extrapolating the plot of rr/C vs. C. Meyerhoff and Shimotsuma3 concluded that Mn, determined by membrane osmometry in o-chlorophenol and m-cresol, is less reliable because of permeation of low molecular weight components through membrane (Sartorius ultracellafilter allerfeinst grade), which was indirectly deduced from the experimental fact that Mn by membrane osmometry is larger than Mn by end group analysis. In this study, for both PET and PEPC solutions, rr value was maintained constant at least several hours and the height of the solvent cup for solvent/solvent combination was not significantly variated.…”
Section: Fractionationmentioning
confidence: 99%
“…Figure 3a and b show the double logarithmic plot of [11] and Mn of PET and PEPC in ochlorophenol and a mixture of P/T (1/2, w/w). The following MHS equations were obtained from viscosity data in Figure 3 by the least square method, where [11] is expressed in ml/g. .,.…”
Section: Solution Viscositymentioning
confidence: 99%
See 3 more Smart Citations